Land Subsidence Monitoring From ALOS/PALSAR Data By Using D-InSAR Technique In Semarang City, Indonesia - Parwata, I Nyoman Sudi; Ogawara, Kakuji; Tanaka, Tasuku; Osawa, Takahiro (International Journal of Environment and Geosciences; Vol 3 No 1 (2019), 2019)
This research was focused to estimate land subsidence in Semarang City by using DInSAR Method during 2007-2010 which is based on ALOS-PALSAR data. Three pair of SAR images were processed to detect land subsidence during 2007-2010. On the other hand, three pairs of SAR images (with small perpendicular baseline and very short interval time observation) were processed to generate Digital Elevation model (DEM). This DEM used to remove topographic phase in DInSAR processing. The land subsidence in Semarang City mostly appears in Northern area (main city), with maximum subsidence value which is derived by using DInSAR Method is about -4.8 cm/year (2007-2008), -8.1 cm/year (2008-2009), and -9.9 cm/year (2009-2010). The average is 7.6 cm/year (2007-2010). The subsidence result by using DInSAR technique was compared with GPS data which was available during 2008-2011. The coefficient determination between DInSAR and GPS method is about 0.65 for 2008-2010. Its mean DInSAR method has a good accuracy and reliable to use for land subsidence monitoring in wide area. The main causes land subsidence in Semarang City is probably due to load of building structure and over extraction of ground water. The number of registered drilled wills increased rapidly during early 1990s especially is industrial areas. The total drilled wells are 1050 units in 2000s.